Applying Mind’s Eye Strategy to Improve Students' Reading Comprehension at the Second Year Students of SMAN Binaan Khusus Dumai - Barruansyah, Rauf Tetuko (J-SHMIC : Journal of English for Academic, 2017)
Based on the writer’s preliminary study, it was found that the students reading comprehension was not reach the standard score. This problem was caused by some factors, for examples; the way of teaching was not suitable with the material, the level of text difficulty was too “high”. Hence, the writer was interested in carrying out the research. It was administered at SMAN Binaan Khusus Dumai. The subject of the research was the second year students, and the object of this research was the Effect of applying Mind’s Eye strategy. The design of this research was Quasi-experimental design. In collecting the data, writer used test. The population of this research was all of the second year students. The writer used cluster random sampling by taking two classes as sample; XI IPS.1 consisted of 32 students as experimental group, and XI IPS.2 consisted of 32 students as control group. To analyze the data, the writer adopted independent sample t-test formula by using SPSS 20 version. Based on the data analysis, consideration Sig (2 tailed) t0= 0,00 is lower than Sig (2 tailed) Ttable= 0.05 It means Ha is accepted and H0 is rejected. So, it can be concluded that there is a significant difference of using mind’s eye strategy to improve students’ reading comprehension at SMAN Binaan Khusus Dumai. Keywords: Minds’ Eye Strategy, Reading Comprehension.